2021
DOI: 10.3390/cells10040941
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells: Neglected Modulators of Peripheral Immune Responses and Neuroinflammation in Mood Disorders?

Abstract: Affective disorders (AD) including major depressive disorder (MDD) and bipolar disorder (BD) are common mood disorders associated with increased disability and poor health outcomes. Altered immune responses characterized by increased serum levels of pro-inflammatory cytokines and neuroinflammation are common findings in patients with AD and in corresponding animal models. Dendritic cells (DCs) represent a heterogeneous population of myeloid cells that orchestrate innate and adaptive immune responses and self-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 270 publications
(185 reference statements)
0
1
0
Order By: Relevance
“…В частности, у пациентов с БАР наблюдается большая атрофия в префронтальной, височной и затылочной коре [55]. Также большой интерес представляет вклад дендритных клеток, одних из ключевых участников процесса нейродегенерации, в механизм нейровоспаления при аффективных расстройствах [56], а начало БА и болезни Паркинсона с депрессивной симптоматики [57,58] может указывать на первые проявления активации микроглии уже при аффективных нарушениях [59,60]. Это дает основания предполагать возможность разработки этиологически обоснованных маркеров психической патологии.…”
Section: о б з о р ыunclassified
“…В частности, у пациентов с БАР наблюдается большая атрофия в префронтальной, височной и затылочной коре [55]. Также большой интерес представляет вклад дендритных клеток, одних из ключевых участников процесса нейродегенерации, в механизм нейровоспаления при аффективных расстройствах [56], а начало БА и болезни Паркинсона с депрессивной симптоматики [57,58] может указывать на первые проявления активации микроглии уже при аффективных нарушениях [59,60]. Это дает основания предполагать возможность разработки этиологически обоснованных маркеров психической патологии.…”
Section: о б з о р ыunclassified
“…Human milk contains a relatively high concentration of macrophages and a plethora of immune factors (cytokines, chemokines, and their receptors) with the potential to interact with microglia (the primary phagocytic cells of the central nervous system) and other brain immunocompetent cells, including astrocytes (Bilbo and Schwarz 2009;Salvador, de Lima, and Kipnis 2021). There are direct physical interactions between immune cells (dendritic cells) and the nervous system (vagus nerve) during lactation and, in fact, it has been suggested that dendritic cells may act as modulators of neuroinflammation in mood disorders (Leite Dantas et al 2021).…”
Section: Immune Cellsmentioning
confidence: 99%